SEXUAL UNDERREPRESENTATION IN ASEAN LITERATURE - Piayura, Orathai (PEOPLE: International Journal of Social Sciences, 2016)
This article is a part of the qualitative research entitled Gender and Sexuality in ASEAN Literature. The purpose of the article is to illustrate the underrepresentation of sexuality in the literature from one of ASEAN countries, Myanmar. The scope of the study was the SEA (South East Asia) Write Awarded Literature. The selected literature was analyzed by gender and sexuality framework. The study found that the SEA Write Awarded literature was expected to represent the ideological society realistically. Therefore, the issue of sexuality was underrepresented in this category of literature because sexual issue was perceived as nonsense and insignificant.